THE USE OF SYMBOLIC IMAGES IN ABDUQAYUM YULDOSH’S STORIES - Yodgorjon Zokirjanov (Journals Park Publishing, 2024)
This article analyzes the issue of symbolism in the stories of writer Abduqayum Yuldoshev. Also, the system of images and the artistic function of symbolic images in the writer’s stories are also researched.
Keywords: image, genre, plot, writer, literary theory, symbolism, novel.